A 70-year-old Woman with Necrotic Wound Complications Following a Snake Bite - Sutanto, Heri; Tri Maharani; Siem, Rochelle Vernique (Universitas Brawijaya, 2024)
Snake bites pose a significant public health issue in Indonesia, leading to high morbidity and mortality rates. Proper identification of snake species and timely management are crucial. A 70-year-old woman was admitted to the emergency department 1.5 hours after being bitten by a snake. Initial management included applying a tourniquet and symptomatic treatment. However, local envenomation signs, such as edema and bullae, developed within 24 hours. Due to financial constraints, the patient could not receive continuous care, leading to complications, including necrosis and signs of secondary infection during follow-up. This case underscores the importance of early intervention and proper wound management in snake bites, particularly when the species is unidentified. Close monitoring is essential, as symptoms may evolve over time. Educating the patients and public regarding signs of necrosis and proper initial treatment is necessary. Effective management of snake bites requires a comprehensive approach, including prompt medical attention and ongoing education to reduce complications and improve patient outcomes. Keywords: Snake bite, envenomation, wound management, public health